Roles of inflammatory cell infiltrate in periprosthetic osteolysis - Panez-Toro, Isidora; Heymann, Dominique; Gouin, François; Amiaud, Jérôme; Heymann, Marie-Françoise; Córdova, Luis A. (Frontiers in Immunology, 2023)
Classically, particle-induced periprosthetic osteolysis at the implant-bone interface has explained the aseptic loosening of joint replacement. This response is preceded by triggering both the innate and acquired immune response with subsequent activation of osteoclasts, the bone-resorbing cells. Although particle-induced periprosthetic osteolysis has been considered a foreign body chronic inflammation mediated by myelomonocytic-derived cells, current reports describe wide heterogeneous inflammatory cells infiltrating the periprosthetic tissues. This review aims to discuss the role of those non-myelomonocytic cells in periprosthetic tissues exposed to wear particles by showing original data. Specifically, we discuss the role of T cells (CD3 + , CD4 + , CD8 + ) and B cells (CD20 + ) coexisting with CD68 + /TRAP -multinucleated giant cells associated with both polyethylene and metallic particles infiltrating retrieved periprosthetic membranes. This review contributes valuable insight to support the complex cell and molecular mechanisms behind the aseptic loosening theories of orthopedic implants.